Prevalence and Incidence of Cardiovascular Disease in Adults With Intellectual Disabilities: A Systematic Review - Leeuw, Marleen J.; Hilgenkamp, Thessa I. M.; Maes‐Festen, Dederieke A. M.; Bindels, Patrick J. E.; Elbers, Roy G.; Oppewal, Alyt (Journal of intellectual disability research, 2025)
ABSTRACT Background Given the high risk of cardiovascular diseases (CVD) in adults with intellectual disabilities (ID), there is a strong need for accurate understanding on CVD prevalence and incidence in this population. This information is important to ensure optimal care and resource allocation. However, systematic reviews on this topic are limited. Therefore, this systematic review aimed to provide a comprehensive synthesis of studies on the prevalence and incidence of CVD in adults with ID, including subgroup data. Method We performed a systematic search in Embase, Medline ALL, Web of Science, Cochrane Central, PsycINFO and Google Scholar up to 21 January 2025, including peer‐reviewed articles on CVD prevalence or incidence in adults with ID. Article screening and data extraction were independently performed by two researchers. Data were synthesised by CVD diagnosis. When available, data were reported separately for different subgroups. The methodological quality was assessed by two independent researchers. This review followed the PRISMA guidelines. Results In 55 articles, prevalence and incidence rates were identified for coronary artery disease (prev 0%–12.9%; inc 2.0–2.8 per 1000py), myocardial infarction (prev 0%–7.9%; inc 0.3–2.8 per 1000py), heart failure (prev 0.8%–18.6%; inc 12.5 per 1000py), cerebrovascular disease (prev 0.7%–15.0%; inc 2.55 per 1000py), stroke (prev 1.3%–17.2%; inc 2.7–3.2 per 1000py), peripheral arterial disease (prev 0.4%–20.7%; inc 1.1 per 1000py), venous thrombosis (prev 0.6%–12.4%; inc 0.8–4.1 per 1000py) and atrial fibrillation (prev 0.8%–6.3%). Subgroup data have been reported based on age, sex, level of ID, aetiology of ID, living circumstances, CVD risk factors, data collection methods and source populations. Overall, higher prevalence and incidence rates were reported in older people and in studies that used physical measurements for diagnosis. Conclusions Due to variability in methodological quality, clinical characteristics and high statistical heterogeneity, drawing conclusions about CVD prevalence and incidence in adults with ID is challenging. Therefore, the subgroup data presented in this review are valuable for identifying rates within specific subgroups. Longitudinal studies along with research employing valid and reliable data collection methods (preferably objective measurements) aligned with studies in the general population, clear reporting of individual CVD diagnoses and subgroup analyses will offer valuable additional insights in future research.